1990
DOI: 10.1002/mrd.1080250403
|View full text |Cite
|
Sign up to set email alerts
|

Cytological effects of the microinjection of antibody to ras p21 in early cleavage Xenopus embryos

Abstract: The presence of two ras-related proteins (22 and 23 kDa) was demonstrated in Xenopus embryonic extracts by selective immunoprecipitation using anti-ras monoclonal antibodies 142-24E05 and Y13-259. We further describe the cytological effects of the microinjection of anti-ras monoclonal antibody Y13-259 into early cleavage blastomeres of Xenopus embryos. Injection of the antibody into a blastomere at the two-, four-, or eight-cell stage caused cleavage arrest in the descendants of the injected blastomere. Light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Finally, PA1 antibody has been used to immunoprecipitate ras-like proteins from various Xenopus cell types. The immunoprecipitated peptides have a Mr -22,500, in agreement with the recently described data on Xenopus ras proteins: Mr -23,000 (Andeol et al, 1990) and Mr -22,000-23,000 (Miron et al, 1990:. Except for a brief report on the presence of ras sequences in the Xenopus genome by Mechali and co-workers (Moreau et al, 1989) and works on Ki type cDNA sequences (Andeol et al, 1990;Baum and Bebernitz, 19901, we have no data about the number and nature of ras genes in Xenopus. From what is known for other species (yeast, Aplysia, and Drosophila) (Barbacid, 1987), we inferred that there is more than one ras gene type in Xenopus also.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, PA1 antibody has been used to immunoprecipitate ras-like proteins from various Xenopus cell types. The immunoprecipitated peptides have a Mr -22,500, in agreement with the recently described data on Xenopus ras proteins: Mr -23,000 (Andeol et al, 1990) and Mr -22,000-23,000 (Miron et al, 1990:. Except for a brief report on the presence of ras sequences in the Xenopus genome by Mechali and co-workers (Moreau et al, 1989) and works on Ki type cDNA sequences (Andeol et al, 1990;Baum and Bebernitz, 19901, we have no data about the number and nature of ras genes in Xenopus. From what is known for other species (yeast, Aplysia, and Drosophila) (Barbacid, 1987), we inferred that there is more than one ras gene type in Xenopus also.…”
Section: Discussionsupporting
confidence: 90%
“…We previously described inhibition of Axolotl egg cleavage following injection of a commercial antibody raised against a c-Ha-ras p21 (Baltus et al, 1988). Miron et al (1990) obtained the same result onXenopus egg, using another anti-ras antibody. By electron microscope analysis, these authors observed in arrested embryos a number of abnormalities related to membrane structure.…”
Section: Discussionmentioning
confidence: 66%
“…However, there are other studies which also implicate the inositol cascade in the cell cycle. The most relevant such study reported that microinjection of an antibody against a p2 ' H-ras onco-protein inhibited cell division in axolotl embryos (2) as well as inXenopus embryos (43). This ras gene protein is found predominantly on the cytoplasmic side of the plasma membrane and is a GTP-binding protein that activates various target enzymes, including PLC which hydrolyzes PIP2 (22,39,45,55) .…”
Section: Discussionmentioning
confidence: 99%